Implicit force control approach for Safe physical Robot-to-Human object handover - Paramin Neranon (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This research focuses on the development of the conceptual frameworks of human-human interaction applied for a robotic behaviour-based approach for safe physical human-robot interaction. The control has been constructed based on understanding the dynamic and kinematic behavioural characteristics of how two humans pass an object to each other. This has enabled a KR-16-KUKA robot to naturally interact with a human so as to facilitate the dexterous transfer of an object in an effective manner. Implicit force control based on Proportional Integral and Fuzzy Logic Control which allows the robot end effector’s trajectory to be moderated based on the applied force in real-time was adopted. The experimental results have confirmed that the quantitative performance of the force-controlled robot is close to that of the human and can be considered acceptable for human-robot interaction. Furthermore, the control based Fuzzy Logic Control was shown to be slightly superior performance compared to Proportional Integral control.